Structural and Functional Cardiac Changes in Children with Wilson Disease - Magd A. Kotb; Fatma Al Zahraa Mostafa; Ahmed M. Badr; Aya S. Hegazy; Mohamed S. Eid; Nahla I. Sabry; Radwa Shamma (Cairo University, Faculty of Medicine, Department of Pediatrics, 2022)
Background: Wilson disease (WD) is an autosomal recessive disease with copper overload. Its clinical picture depends on specific tissue/system damage by the excess copper. Aim of the work: We aimed to study prospectively the phenotypic spectrum of structural and functional cardiac changes among children with WD. Methods: 16 children with confirmed WD underwent electrocardiography (ECG), conventional and tissue Doppler echocardiography. Results: ECG was normal in 11 patients (68.7%), inverted T was detected in 2 (12.5%), ST elevation in 2 (12.5%) while P-pulmonale and inverted T were detected in 1 (6.25%). Five patients (31.25%) had mild and one (6.25%) had severe tricuspid regurgitation. Two girls (12.5%) with WD had underlying congenital heart defects, one had atrial septal defect (ASD) and another had double inlet left ventricle (DILV), malposed great vessels and severe pulmonary stenosis. There was a positive correlation between LV mass and duration of treatment (r=0.559, p=0.030), and a negative correlation between age of onset and LV mass index (r=0.600, p=0.018). There was no significant correlation between age of onset and duration of treatment with myocardial perfusion imaging (MPI) or tissue Doppler parameters. Conclusion: WD in children is associated with cardiac structural and functional changes including congenital structural heart malformations; ASD and DILV. Future research is needed to verify if ASD and DILV in WD are embryonic presentations of copper overload in WD.